Conductive Smart Scaffold for Electrochemical Sensing in Bone Tissue Engineering Applications: A Review - Rusyda Fajarani; Siti Fauziyah Rahman; Armelia Ramandha (Rekayasa, 2026)
Tissue engineering technology using biomaterial-based scaffolds has been developed to support and regulate cellular activities, including cell adhesion, proliferation, migration, and the differentiation of electrically excitable cells through the incorporation of conductive materials. Conductive smart scaffolds have emerged as a promising platform for bone tissue engineering by integrating structural support with electrochemical sensing capabilities. Recent advances have enabled the development of conductive scaffolds integrated with electrochemical sensing systems for real-time, non-invasive monitoring of cellular behavior during bone regeneration. This review analyzes recent developments in electroactive conductive scaffolds and scaffold-based electrochemical sensing platforms for bone tissue engineering applications. A comprehensive literature review was conducted across major scientific databases to identify studies related to scaffold composition, conductive materials, electrochemical characterization methods, sensing strategies, and associated biological responses. The reviewed studies demonstrate that conductive polymers and carbon-based nanomaterials are widely used to enhance scaffold electroactivity and osteogenic performance. Electrochemical characterization techniques, including Cyclic Voltammetry (CV) and Electrochemical Impedance Spectroscopy (EIS), are commonly employed to evaluate scaffold conductivity, redox behavior, and electrochemical stability. Furthermore, conductive scaffold-based electrochemical sensing systems have been successfully applied to monitor cell viability, adhesion, proliferation, mineralization, and osteogenic differentiation in a label-free, non-destructive manner. The integration of conductive biomaterials with electrochemical sensing platforms enables precise monitoring of cellular activities through changes in electrical signals, impedance, and electrochemical responses. Overall, conductive smart scaffolds represent a promising multifunctional strategy for advancing bone tissue engineering by combining biocompatibility, electroactivity, regenerative capability, and real-time biosensing within a single scaffold system.